FASD based on BSC method for distribution networks. Issue 24 (20th November 2019) - Zheng, Ze‐Yin; Guo, Mou‐Fa; Yang, Nien‐Che; Jin, Tao
Abstract : A Petersen coil was used as a passive arc‐suppression device (ASD) to mitigate ground‐fault current when a single‐phase‐to‐ground fault occurred in distribution networks. However, passive ASDs cannot compensate for the active and harmonic components of ground‐fault current. Furthermore, a massive residual ground‐fault current would endanger human life and the reliable operation of distribution networks. To overcome the shortcomings of passive ASDs, a three‐phase flexible ASD (FASD) with a three‐phase cascaded H‐bridge topology was presented. A three‐phase FASD connected to a bus bar of distribution networks was employed to compensate for the ground‐fault current. In this study, the FASD with the backstepping control (BSC) based on current‐compensation principle was proposed to completely eliminate the ground‐fault current. The effectiveness of the proposed FASD with the BSC method was verified using the simulation and experimental results.